KAJIAN POTENSI SUMBER ENERGI BIOGAS DARI KOTORAN TERNAK UNTUK BAHAN BAKAR ALTERNATIF DI KECAMATAN KALIREJO KABUPATEN LAMPUNG TENGAH - Untung Surya Dharma; Kemas Ridhuan (TURBO [Tulisan Riset Berbasis Online], 2014)
Biogas is a source of energy that is derived from the decomposition of organic matter by microorganisms in the absence of oxygen (anaerobic) to produce a mixture of several gases are methane (CH 4) and carbon dioxide (CO 2).Biogas can be made from many types of waste material and the rest aniani4d , a kind of garbage, livestock waste, agricultural waste and others.Things to consider in the development of biogas energy source so that the principle of availability of sustainable biogas as an alternative fuel can be met is a local or regional potential to produce biogas.Communities in the District Central Lampung regency Kalirejo many who maintain livestock.Waste from livestock manure is especially very disturbing and detrimental to health, it is encouraging to capitalize upon the waste as feedstock for biogas production.To assess the potential of biogas energy sources are needed data about the amount of livestock manure every day, in this study is the dung of cows, goats and chickens.Fermentation process for the three types of dirt inside the reactor each trial was conducted to determine the length / time effective and energy biogas produced.From the field data known total number of chickens are farmed as much as 176.264 , goat 12.345and cow 4.488 tail.Manure produced by 1 chicken, 1 goats and one cow in a row that is 0.055 kg / day, 0.98 kg / day and 19.5 kg / day.While the testing laboratory, known Biogas produced from each of 20 kg of dung that chicken manure yield of 2.04 m 3, cow dung yield of 0.56 m 3 and 0.76 m 3 cow dung.From field data and laboratory testing can be calculated local potential in providing sustainable biogas in District Kalirejo Kalirejo Central Lampung regency, namely the potential of biogas from chicken manure at 988.84 m 3 / day, goat manure at 338.75 m 3 / day and cow manure at 3325.61 m 3 / day.So the total potential of biogas that can be generated is equal to 4653.2 m 3 / day.Keywords: Biogas, local potentials, livestock manure, the total potential of biogas.